Incidence Analysis of Public Support to the Private Education Sector in Côte d'Ivoire - Sakellariou, Christos N., 20./21. Jh. 20./21. Jh (The World Bank, 2004)
Sakellariou and Patrinos analyze the equity effects of public subsidization of private schools in Côte d'Ivoire, update previous analyses, and attempt to assess how efficiently public spending is targeted. The subsidy per student in private (and public) schools increases at higher quintiles. Students from families in the highest quintile receive more than twice the subsidy received by students from families in the lowest quintile, compared with four times more in the case of students attending public schools. However, the subsidy system is progressive as there is a clear tendency for the share of family education expenditure covered by subsidies to decline at higher quintiles. This element of progressivity is stronger in the case of private school attendance. This paper—a product of the Education Sector Unit, Latin America and the Caribbean Region—is part of a larger effort in the region to evaluate education policies